The legacy of Soo Kim Lan: a tribute to Malaysia's first woman doctor / Associate Professor Dr. Soo Kum Yoke - Soo, Kum Yoke (Academy of Language Studies, Universiti Teknologi MARA Negeri Sembilan Branch, Rembau Campus, 2024)
In the annals of Malaysian history, a shining beacon of inspiration stands tall, illuminating the path for generations to come. The story of Malaysia's first woman doctor deserves to be etched in the hearts and minds of all, for her legacy transcends the boundaries of gender and embodies the unwavering spirit of service and equality. Reminiscent of the pioneering women doctors who made significant strides in Korea's modernization such as Esther Park, my grandaunt's journey was marked by a deep-seated commitment to the well-being of her community. She too, recognized the importance of addressing the unique healthcare needs of women, but her vision expanded beyond the confines of gender, encompassing the holistic care of all individuals. Her unwavering dedication and competence earned her the admiration and respect of her peers, and she became a true role model, inspiring generations of women to follow in her footsteps.